Ready for a Career in the Agriculture Sector in Egypt? Perceptions of Students, Faculty, and Employers on the Value of Essential Technical and Employable Skills - Ramjee P. Ghimire; D. Hashini Galhena Dissanayake; Karim Maredia; Nanda P. Joshi; Paul Ebner (Education Sciences, 2022)
High unemployment among college graduates has been a big concern in Egypt for many years now. Mismatch in technical competencies and lack of job-oriented skills and inequity in education and career by gender pose a major constraint for Egyptian youth to find employment. Information about whether the gender of the mentor has any effect on the quality of mentoring is also nonexistent. Using web and in-person survey data among agricultural students, faculty, and potential private sector agribusiness employers, this paper attempts to investigate whether there are any significant differences in the application and use of career guidance by male and female students to prepare for careers prospects and align with the industry needs. The results will validate if there are significant differences in between male and female faculty in their perception of relevance of technical and employable skills as well as the use and application of career guidance and mentoring by students to increase their prospects with employers. The findings will be used to develop interventions that would help align student skills with employer expectations as well as upgrade faculty competencies.